CLP : Unoriginal - Dawson Alternative School (2020)
Number of pages: 24

Aivik - Writers in the Community (2020)
Number of pages: 16

Entrepreneurs and Artists in the Time of COVID-19 - Youth Employment Services (YES) (2020)
In response to the detrimental effects of COVID-19, Canadian governmental agencies and other organizations have deployed multiple programs to support local entrepreneurs and their businesses. In the current evolving situation, it’s hard to know where to turn. This document contains some of the currently available programs and resources for entrepreneurs and will be updated periodically. Last updated on July 27, 2020.

Teenage Vibes - Dawson Alternative School (2020)
Number of pages: 14

Validate ARTS2U Business Model - VABM - English Language Arts Network (ELAN) (English-Language Arts Network (ELAN), 2020)
With this research, the ELAN ARTS2U project has described comprehensive business and revenue modelling for the digital events listings service in the arts sector. This project supports science research of new technology models for the arts sector with potential to enhance and promote increased tourism in Canada. It is building on the scientific premises of metadata, natural language processing, machine learning and AI to the benefit of Canadian creative productions. It improves the potential for investment in Canadian locations and has the potential to develop employment positions in the high skilled technology job market. ARTS2U and its national collaborators are building an efficient and competitive Arts sector marketplace. By driving innovation in the arts and creative sectors, the ARTS2U initiative demonstrates that Canada is a leader in the international creative economy.

DCCADI : Developing Connections and Collaborations Among Digital Initiatives : Final Report to: Canada Council - Digital Strategy Fund - English Language Arts Network (ELAN) (English-Language Arts Network (ELAN), 2020)
With the Developing Connections & Collaborations Among Digital Initiatives (DCCADI) project, ELAN’s ARTS2U has worked with Canada-wide digital initiatives in the arts. ELAN has forged strong relationships among similar projects with the review of data structures, research of commonalities, strategic alignments, and best practices. The ARTS2U - DCCADI initiative provides recommendations for the benefit of Canadian artists and organizations seeking to have increased visibility on digital platforms. The shift to digital platforms has had resounding impacts on creators of art in Canada. Visibility and find-ability are key concepts when artists are seeking to connect with their audiences. The key ideas are central to artists as they strive to achieve sustainable business models in a world powered by AI, machine learning, and structured data. The distribution of arts events and products is currently dominated by social media and technology companies, and Canadian artists are largely not in control of their capacity to reach audiences.
Keywords: Official Language Minority Community (OLMC)

Winter/Spring 2020 Program Book : January 2020 - August 2020 - Youth Employment Services (YES) (2020)